2010
DOI: 10.1073/pnas.1010154107
|View full text |Cite
|
Sign up to set email alerts
|

Modeling electrical activity of myocardial cells incorporating the effects of ephaptic coupling

Abstract: Existing models of electrical activity in myocardial tissue are unable to easily capture the effects of ephaptic coupling. Homogenized models do not account for cellular geometry, while detailed spatial models are too complicated to simulate in three dimensions. Here we propose a unique model that accurately captures the geometric effects while being computationally efficient. We use this model to provide an initial study of the effects of changes in extracellular geometry, gap junctional coupling, and sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(114 citation statements)
references
References 21 publications
9
98
1
Order By: Relevance
“…This time course may also be shorter than the time required for new G j formation (20), especially in intact tissue. Finally, cardiac conduction may involve alternative modes of intercellular coupling that are not exclusively dependent on gap junctions (25,37). Irrespective of the mechanism, V IS plays an important role in modulating conduction.…”
Section: The -V Is Relationshipmentioning
confidence: 99%
“…This time course may also be shorter than the time required for new G j formation (20), especially in intact tissue. Finally, cardiac conduction may involve alternative modes of intercellular coupling that are not exclusively dependent on gap junctions (25,37). Irrespective of the mechanism, V IS plays an important role in modulating conduction.…”
Section: The -V Is Relationshipmentioning
confidence: 99%
“…The fact that transmembrane sodium channels are concentrated around the ICDs 28,32 has been seen as providing a mechanistic framework for ephaptic transmission. Computer models of 1D myocyte strands in which sodium channels were colocated with gap junctions at the interface between adjacent cells 32,33 suggest that ephaptic coupling increases CV at low gap junction conductivity and vice versa. One interpretation of these findings is that both mechanisms act in concert to stabilize impulse transmission between myocytes.…”
Section: Impulse Transmission Between Myocytesmentioning
confidence: 99%
“…Alternatively, they may be able to have extracellular resolution much less than intracellular resolution. For work developing a purely-microscale version of such a generalization, see Lin and Keener (2010).…”
Section: Resultsmentioning
confidence: 99%
“…Further, in a subsequent study, they also found that gap-junctional coupling was essentially abolished in isolated cell pairs extracted for Cx43-null ventricular tissue (Yao et al 2003). These findings are surprising because gap junctions are generally accepted as the primary mechanism of normal cardiac electrical communication (Rohr 2004), and they suggest that there are important electrical coupling mechanisms in cardiac tissue besides gap-junctionally mediated coupling (Sperelakis and Mann 1977;Picone et al 1991;Ramasamy and Sperelakis 2007;Mori et al 2008;Copene and Keener 2008;Hand and Peskin 2010;Hand and Griffith 2010;Lin and Keener 2010).…”
mentioning
confidence: 95%